2013
DOI: 10.1589/jpts.25.981
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hand Position Changes on Electromyographic Activity of Shoulder Stabilizers during Push-up Plus Exercise on Stable and Unstable Surfaces

Abstract: [Purpose] The purpose of this study was to determine the effect of hand position changes on electromyographic activity of shoulder stabilizers during push-up plus exercise (PUPE) performed on both stable and unstable surfaces. [Subjects] This study was performed on a cohort of 20 normal adults divided into an unstable surface group (USG) (n=10) and a stable surface group (SSG) (n=10). [Methods] A sling device was used to provide an unstable surface, and a push-up bar was used to provide a stable surface. PUPEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 11 publications
(10 reference statements)
0
40
0
1
Order By: Relevance
“…Twelve articles focused on the effects of the base of support during PUP exercises. 9,[15][16][17][18][19][20][21][22][23]51,52 After further checking for the meta-analysis, 1 article was excluded due to insufficient data for the means and standard deviations. 51 Therefore, 11 articles were included in this meta-analysis for analyzing the differences in SA and UT muscle activity during the PUP performed on stable and unstable surfaces.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve articles focused on the effects of the base of support during PUP exercises. 9,[15][16][17][18][19][20][21][22][23]51,52 After further checking for the meta-analysis, 1 article was excluded due to insufficient data for the means and standard deviations. 51 Therefore, 11 articles were included in this meta-analysis for analyzing the differences in SA and UT muscle activity during the PUP performed on stable and unstable surfaces.…”
Section: Study Selectionmentioning
confidence: 99%
“…[12][13][14] After finding that the standard PUP (SPP) and knee PUP exercises induced the highest SA and lowest UT : SA EMG measures, Ludewig et al 8 recommended these exercises for selective SA strengthening. Researchers 5,9,[15][16][17][18][19][20][21][22][23][24][25][26] have investigated whether the PUP exercise performed on different unstable bases stimulated mechanoreceptors and increased SA EMG activity, thereby enhancing shoulder-joint stabilization. The use of unstable or stable surfaces during the PUP exercise is under debate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are different opinions regarding whether the push-up plus exercise should be conducted on stable or unstable support. Lee et al (2013) reported that performing the exercise on unstable support was more effective at increasing muscle activity and stimulating shoulder joint proprioceptors.…”
Section: ⅰ Introductionmentioning
confidence: 99%